Diagnóstico fitosanitario y recomendaciones de manejo agroecológico de plagas en comunas de las provincias de Guayas y Santa Elena. - Ventura Cruz, Miguel (2015)
This study was carried out in ten communes in Guayas and Santa Elena provinces in the period between January and May 2011, under the PIDAASSE Project, which included the visit and tour of the various plots of the project’s villagers with the objective to build information about what cultivations are developed in the sector, and what are the plant damages present in the area, either by pests or diseases, thereby facilitating the development objectives such as the assessment of agricultural management in crops, identifying key pests, establishment an agro-ecological pest ma¬nagement, MAP, with the implementation of different schemes depending on the crops to develop. The methodology used in the study was recommended by the INICA and Plant Health Department, where sampling areas of different crops production was performed, evaluating the damages and determining the causative agents. Also the paper shows interviews to the villagers to have more knowledge of the situation in their areas of production. As diagnostic’s result the paper shows different schemes for the implementation of MAP in each of the following crops: cassava, plantain, vegetables, beans, corn, cucurbits and other.